Dietetics Students' Perceived Facilitators and Barriers to Clinical Training in Malaysia: A Qualitative Theory-Guided Analysis - Eshamuddin, Nur Amirah Nabihah; Hao, Lim Jun; Ying, Chin Yi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study explored barriers and facilitators experienced by Malaysian dietetics graduates during clinical training in local healthcare settings. A qualitative study with phenomenological design was conducted on fifteen purposely selected fresh dietetics graduates, with a mean age of 24.7±0.8 years from seven local universities. Virtual interviews were conducted via the Cisco Webex and were verbatim transcribed and thematically analyzed using NVivo 12 Plus software. Data collection continued until data saturation was reached. Nine Theoretical Domain Frameworks (TDF-derived domains), comprising of 1) knowledge, 2) skills; 3) belief about capabilities; 4) intention; 5) goals; 6) memory, attention, and decision process; 7) environmental context and resources; 8) social influences; and 9) emotions domains, was utilized to develop open-ended questions in the semi-structured questionnaire. Within these domains, frequently associated sub-themes of perceived facilitators were identified: early preparation and comprehension. Pre-clinical classes that involve solving diverse and challenging cases equip students with practical understanding of clinical training. Curriculum-based university clinics offer valuable insights into hospital dietetics practice. Resources availability is crucial for effective Nutrition Care Process (NCP) implementation and aids in evidence-based nutrition counseling. Conversely, the factor that hinders clinical training reported by dietetics graduates is a lack of knowledge and readiness, particularly concerning their perceived knowledge before clinical training. Dissatisfaction also arises from challenges in building rapport, gathering patient information during counseling, and difficulties in assessing dietary recall with patients from diverse cultural backgrounds, affecting their readiness for dietetics practice and therefore, highlighting the need to enhance multicultural knowledge and cultural competency training among dietetics students. The findings from this study may assist in developing strategies to promote impactful experiences and enhance dietetic students' preparedness for clinical practice.